Cycles of Creation and Destruction of Production and Technological Capabilities in Latin America. - Katz, J (SLPTMD (Department of International Development, University of Oxford), 2007)
For more than three decades now Latin American countries have introduced marketoriented structural reforms, opening up their economies to foreign competition, de-regulating markets, and privatising economic activities. These policy reforms involved a major departure from the policy regime that prevailed in the region during the immediate post war period. The new policies –together with the rapid process of globalisation of the world economy that obtained throughout the 1990’s– induced a major transformation of the social, economic and institutional environment of each one of the countries in the region, as a result of which Latin American economies have undergone major changes in production structure, international competitiveness, institutions and technological capabilities.